En contra de la ratificación judicial: el caso peruano - Villanueva, Rocío (2025)
This article proposes that judicial performance revalidation be eliminated from the Peruvian Constitution because it violates the principle of judicial independence and an individual’s right to be judged according to the law. The author sustains that it is a problematic and unreasonable institution. In the article, the jurisprudence of the Constitutional Tribunal is reviewed, since over the course of more than twenty years it has varied with respect to the legal nature of the judicial performance revalidation process, the rights of magistrates subjected to that process and the legal consequences in the judicial career of the decision against judicial performance revalidation. The article also contains a review of the jurisprudence of the Inter-American Court of Human Rights on judicial independence, emphasizing that the principle tries to control the reasons based on which judges decide cases. Additionally, it presents the judicial performance revalidation procedure, especially in relation to the aspects being evaluated, to the documentation asked of judges and to some of the criteria used in the evaluation. It also contains judicial revalidation figures for the 2001-2021 period and analyzes whether judicial performance revalidation fulfills its constitutional purposes or, on the contrary, is unreasonable and contributes to judges making decisions for the wrong reasons.